THE EFFECT OF CHARACTERISTICS GOOD CORPORATE GOVERNANCE ON AREA OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Johny Subarkah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine the effect of the characteristics of good corporate governance on the disclosure of corporate social responsibility (CSR). The population is manufacturing companies listed on the Indonesia Stock Exchange 2020 and a sample of 87 (eighty seven) companies using purposive sampling technique in sampling. The technique of collecting data for this research is from the Indonesia Stock Exchange website, namely www.idx.co.id, company websites and various sources that are relevant to the research topic. Hypothesis testing using multiple linear regression, t test (partial test), F test (simultaneous test), and the coefficient of determination test. The results showed that partially the board of commissioners variable, auditor variable, and public share ownership variable had no effect on the extent of corporate social responsibility (CSR) disclosure, while the audit committee variable affected the extent of corporate social responsibility (CSR) disclosure. The test results based on the simultaneous test show that the variable of the board of commissioners, the variable of the audit committee, the variable of the auditor, and the variable of the public stock have no effect on the extent of corporate social responsibility (CSR) disclosure. Keywords: CSR, characteristics, good corporate governance, manufacturing companies, BEI